STUDI FITOKIMIA DAN FARMAKOLOGI DAUN MANGKOKAN (Nothopanax scutellarium) - Adinda Putri Sabrina; Evi Tania; Nurhalifah Nurhalifah; Robby Alvian; Santika Citra Veronita; Shella Imka Puji; Siti Nuryamah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Nothopanax Scutellarium (Araliaceae family), commonly known as the leaves of the bowl, is a medicinal plant that has many pharmacological properties. The leaves of this plant have various uses in traditional medicine for a number of diseases. There are so many substances contained in this plant such as flavonoids, saponins, tannins, phenolics, alkaloids, steroids and so on. Several studies have demonstrated the pharmacological exploration of Nothopanax Scutellarium as a Culex sp mosquito larvicide, diuretic, anti-kidney stone solubility, anti-aging, burn healer, anti-oxidant and anti-bacterial which were carried out experimentally both in vivo and in vitro.